Changes in the sialylation and sulfation of secreted thyrotropin in congenital hypothyroidism. - Gyves, P W (1990)
We have examined the oligosaccharide structure of secreted thyrotropin (TSH) in perinatal and mature rats with congenital primary hypothyroidism. Rat pituitaries from euthyroid control animals and those rendered hypothyroid by methimazole treatment were incubated with [3H]glucosamine in vitro. Secreted TSH was purified, and oligosaccharides were enzymatically released and characterized by anion-exchange HPLC. In perinatal hypothyroid animals compared with control animals, oligosaccharides from TSH alpha and beta subunits contained more species with three or more negative charges. Moreover, perinatal hypothyroid animals demonstrated a dramatic increase in the ratio of sialylated to sulfated species within oligosaccharides of the same negative charge (2.9- to 7.4-fold increase for TSH-alpha; 15.1- to 25.5-fold increase for TSH-beta). In mature hypothyroid 9-week-old animals compared with control animals, changes were less pronounced, suggesting that endocrine regulation of oligosaccharide structure is dependent upon the maturational state of the animal. These changes were specific for TSH because glycosylation of free alpha subunit (synthesized by the thyrotroph and gonadotroph) and of total glycoproteins was minimally altered by hypothyroidism. Together, these data provide direct evidence and characterization of specific changes in the structure of a secreted pituitary glycoprotein hormone occurring as a result of in vivo endocrine alterations during early development. Moreover, they provide a potential structural basis to explain the delayed clearance of both TSH and the gonadotropins with end-organ deficiency, which may have important implications for the in vivo biological activities of these hormones. Specifically, such posttranslational changes may be an important adaptive response to prevent the consequences of endocrine deficiency during early development.